Effect of Integrated Neuromuscular Inhibition Technique on Frozen Shoulder - Amir A. Khan1, Smita Patil2, Khushboo Bathia3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Frozen shoulder is a painful condition of the joint capsule leading to loss of range of motion of the joint. Due to pain and inability to move the involved shoulder, patients tend to avoid any movement of the involved arm. This leads to formation of Myofascial Trigger points and tender points in the muscles. This overall makes the prognosis more challenging as the focus is mostly on the joint. Integrated Neuromuscular Inhibition Technique is a soft tissue manipulation technique that has been proven to relieve trigger and tender points. Although proven to be efficiently effective in many disorders, this technique is not as such practiced as a common and regular approach by professionals. Thus, this technique was undertaken and experimented on Frozen Shoulder. Objectives: Objectives of the study were to determine the effect of Integrated Neuromuscular Inhibition Technique in Frozen Shoulder and compare the effect of Integrated Neuromuscular Inhibition Technique with conventional treatment in frozen shoulder. Material and Method: In this experimental study, 40 Frozen Shoulder subjects were assessed using Visual Analogue Scale (VAS), Goniometer for Range of Motion (ROM) and Shoulder Pain and Disability Index (SPADI). The subjects were divided into 2 groups, Group A Included 20 subjects treated with Hot moist pack, Therapeutic Ultrasound, Exercises and Capsular Stretching and Sleeper stretch. Group B included 20 subjects treated with Hot moist pack, Therapeutic Ultrasound, Exercises and Capsular Stretching and Sleeper stretch and Integrated Neuromuscular Inhibition Technique. Results: Within group statistical analysis of VAS, ROM and SPADI for both the groups were found to be extremely significant with a p value of <0.0001. On comparing between the two groups post treatment, there was extremely significant difference in Group B as compared to Group A regarding VAS (p=0.002), very significant difference for SPADI (p=0.0047), FLEXION ROM (p=0.0076) and ABDUCTION ROM (p=0.0026). But, there was no significant difference between the two groups regarding MEDIAL ROTATION ROM (p=0.1772) and LATERAL ROTATION ROM (p=0.7602). Conclusion: The study concluded that Integrated Neuromuscular Inhibition Technique and Conventional Physiotherapy are both effective in the management of Frozen Shoulder. Also, Integrated Neuromuscular Inhibition Technique given with Conventional Treatment is significantly more effective as compared to conventional treatment alone on pain, range of motion and functional status of Shoulder and thus Alternate Hypothesis accepted